Evaluasi dan Rekomendasi Srategi: Tinjauan Atas Upaya Resiliensi Sekolah Menengah Atas di Indonesia dalam Realisasi Kebijakan Zonasi - Sesanti, Alma'idah Hayuning; Imron, Ali; Sunarni, Sunarni (Universitas Negeri Padang, 2025)
In Indonesia, the New Student Admissions (PPDB) zoning system, regulated by the Minister of Education and Culture Regulation Number 17 of 2017, continues to spark debate. This policy aims to improve access to education by minimizing travel distances, reducing transportation costs, and facilitating parental involvement. However, it also presents challenges, such as declining quality in prestigious schools, reduced student motivation, and perceived inequities in the system. This article explores the zoning policy's impacts at the senior secondary school (SMA) level, highlighting both its benefits and drawbacks while proposing solutions to enhance school quality resilience using the PDCA (Plan-Do-Check-Act) cycle. Employing a descriptive qualitative approach, the study reviews 42 articles sourced from Publish or Perish, BASE, Google Scholar, and Semantic Scholar. The findings underscore the need for targeted strategies to address the policy’s shortcomings and optimize its implementation to ensure equitable and high-quality education for all.